Benefits Of Using Proverbs in Differentiated Instruction (Eurasian Journal of Humanities and Social Sciences, 2024)
This article discusses the significance of English proverbs in differentiated instruction, highlighting their role in enhancing students' cultural awareness, language development, critical thinking, and moral values. It explores how proverbs can be effectively integrated into various teaching methods and provides practical strategies for their application. The article also addresses potential challenges in using proverbs and offers solutions for overcoming them. Ultimately, proverbs are viewed as valuable tools that make the learning process more effective and engaging for students.